2017
DOI: 10.3390/microorganisms5030063
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting for Exopolysaccharides from Deep-Sea Hydrothermal Vent Bacteria: Relationship between Bacterial Diversity and Chemical Diversity

Abstract: Many bacteria biosynthesize structurally diverse exopolysaccharides (EPS) and excrete them into their surrounding environment. The EPS functional features have found many applications in industries such as cosmetics and pharmaceutics. In particular, some EPS produced by marine bacteria are composed of uronic acids, neutral sugars, and N-acetylhexosamines, and may also bear some functional sulfate groups. This suggests that they can share common structural features with glycosaminoglycans (GAG) like the two EPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 64 publications
2
16
1
Order By: Relevance
“…The EPS yield was higher in strain PQQ-42 (0.36 g l −1 ) than in strain PQQ-44 (0.15 g l −1 ), which confirmed the results observed by scanning electron microscopy. These EPS production values are similar to those obtained with other marine bacteria 42,43 .
Figure 5Exopolysaccharide production in strains PQQ-42 and PQQ-44. Uranyl acetate staining of strains PQQ-42 ( a ) and PQQ-44 ( b ) as observed by transmission electron microscopy.
…”
Section: Resultssupporting
confidence: 86%
“…The EPS yield was higher in strain PQQ-42 (0.36 g l −1 ) than in strain PQQ-44 (0.15 g l −1 ), which confirmed the results observed by scanning electron microscopy. These EPS production values are similar to those obtained with other marine bacteria 42,43 .
Figure 5Exopolysaccharide production in strains PQQ-42 and PQQ-44. Uranyl acetate staining of strains PQQ-42 ( a ) and PQQ-44 ( b ) as observed by transmission electron microscopy.
…”
Section: Resultssupporting
confidence: 86%
“…In contrast to the EPS produced by Alteromonas and Pseudoalteromonas species, the HE800 EPS produced by Vibrio diabolicus is a linear non-sulfated polysaccharide composed only of uronic acids (GlcA) and N-acetyl hexosamines: N-acetyl-glucosamine (GlcNAc) and N-acetyl-galactosamine (GalNAc) [16,17]. A recent study reported by Delbarre-Ladrat et al [18] put forward that general traits of the EPS composition were specific to the bacterial genera with Alteromonas and Pseudoalteromonas species mainly producing EPS rich in neutral sugars and uronic acids with some substituents, such as sulfates, and Vibrio species synthesizing EPS composed of uronic acids and hexosamines.…”
Section: Introductionmentioning
confidence: 99%
“…The marine environment and in particular extreme habitats, such as deep-sea hydrothermal vents constitute a potential resource of unknown bacteria that can synthesize EPS with unique structures (Delbarre-Ladrat, Sinquin, Lebellenger, Zykwinska, & Colliec-Jouault, 2014;Delbarre-Ladrat, Leyva Salas, Sinquin, Zykwinska, & Colliec-Jouault, 2017).…”
Section: Introductionmentioning
confidence: 99%